Aging in community: home- and community-based services clients' use of computers as a protective factor for social isolation and loneliness. Issue 10 (3rd October 2018) - Nilsen, Kari M.; Medvene, Louis J.; Ofei-Dodoo, Samuel; Smith, Rachel; DiLollo, Anthony; Graham, Annette; Nance, Anita
ABSTRACT: Frail older adults are increasingly being cared for in the community via home- and community-based service (HCBS) programs rather than nursing homes. This policy change challenges psychologists, social workers, and all geriatric practitioners to identify risk and protective factors in order to implement community-based policies in ways which promote the well-being of frail older adults. The present small-scale exploratory study focused on the risk factors of social isolation and loneliness, and the potential of computer use to act as a protective factor. Forty HCBS clients were interviewed about their social convoys, social isolation, and loneliness, and their use of computers. Family members made up the largest percentage of participants' social convoys (48%). Forty-two percent of participants were found to be socially isolated or at high risk for social isolation. Twenty-five percent of participants used computers and these participants experienced significantly less loneliness and had significantly larger social convoys. All participants were shown a 2.5 -minute video demonstrating a computer programmed to accommodate older adults and 80% expressed interest in using such a program. Future action research projects are suggested to replicate the study's findings. Such projects could involve collaboration between gerontologists and local area agencies on aging and "service-enriched" affordable senior housing sites.